SISTEM INFORMASI BERBASIS SMS GATEWAY PEMANTAU PERKEMBANGAN KARAKTER SISWA MENGGUNAKAN SKALA LIKERT - Sigit Riyadi; Husni Mubarok (SPIRIT, 2017)
Abstract : using an information about student’s character developing still conventionally. This is done by getting the qualitative data about student’s character through the process of daily observation in the school which is written on student’s and teacher journal colomn without any quantitative instrument. In order to state that the data about student character is accurate and valid, so the researcher create a character test instrument using questionnaire which is processed using likert scale and sent the result to parents by sms gateway. Hopefully this can facilitate teacher to report the students character developing to parents.Keywords : character, skala likert, sms gateway